Mejora continua en el mantenimiento de una línea de producción para una fábrica de productos alimenticios - Hidalgo, Christian (2013)
The production line aims to work with a minimum yield of 88% each programmed week. The problem is that there is no fulfillment with the required production by the Company’s Directive, it also got to have only a 65% of total production. The system indicators of SAM Company detail that the greatest impact reason of the non fulfillment are the technical stoppages. This situation is analyzed by the technical department, which observes the necessity of establish one or several improvements in the maintenance process. As a brief description of the production line, we can say is for bottling of high tempered liquid and viscose characteristic which goes through various steps such as washing, capping and labeling to obtain the end product. Besides, this industry is also dedicated to manufacture and trade food products as chocolate, semi manufactured culinary and cold dressings. The working methodology consists in making an initial diagnosis of the machines, which are the structures of the production line to determine which are the critical parts producing the technical stoppages and an accurately selection of the work to be done in the four weeks scheduled for maintenance. The desired object in the moment that starts the production is to increase the performance of the production line and keep it constant. This research is directed to packaging lines of foodstuffs, but the approach of continuous improvement is applicable in all technical aspects and even more in repetitive problems.